2012
DOI: 10.1007/s00244-012-9786-z
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate Kinase Activity and δ-Aminolevulinic Acid Dehydratase Activity as Biomarkers of Toxicity in Workers Exposed to Lead

Abstract: Lead (Pb(2+)) is a heavy metal that has long been used by humans for a wide range of technological purposes, which is the main reason for its current widespread distribution. Pb(2+) is thought to enter erythrocytes through anion exchange and to remain in the cell by binding to thiol groups. Pyruvate kinase (PK) is a thiol-containing enzyme that plays a key role in erythrocyte cellular energy homeostasis. δ-aminolevulinic acid dehydratase (δ-ALAD) is the second enzyme in the heme biosynthetic pathway and plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…They concluded that the possible threshold value of blood lead for ALAD activity is around 10 µg/dL, and thus, ALAD activity may be usedas a biomarker for evaluation of lead toxicity in humans. Similar results were reported by Fecsa et al; who analyzed lead dose-dependent effects for 18 lead exposed individuals and 12 normal volunteers [21]. Jasim et al also reported a decrease of ALAD activity in battery manufacturing factory workers compared to non-exposed group; furthermore, this decrease became even more evident with increased duration of exposure [28].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…They concluded that the possible threshold value of blood lead for ALAD activity is around 10 µg/dL, and thus, ALAD activity may be usedas a biomarker for evaluation of lead toxicity in humans. Similar results were reported by Fecsa et al; who analyzed lead dose-dependent effects for 18 lead exposed individuals and 12 normal volunteers [21]. Jasim et al also reported a decrease of ALAD activity in battery manufacturing factory workers compared to non-exposed group; furthermore, this decrease became even more evident with increased duration of exposure [28].…”
Section: Discussionsupporting
confidence: 81%
“…For that reason, some researchers have recommended use of ALAD inhibition as an indicator of lead intoxication [12,21,29]. In our study, ALAD activity was significantly lower in women with BLLs ≥ 5 µg/dL compared with those with BLLs below 5 µg/dL.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…In 3 studies, GSH levels decreased in the exposed group (Mohammad et al 2008 ;Feksa et al 2012 ;Kasperczyk et al 2013b ) and were negatively correlated with BLLs in the Lead Exposure and Oxidative Stress: A Systematic Review 226 other study ( r = −0.423; p < 0.001) (Roels et al 1975 ). However, GSH levels increased in the exposed group and were also negatively correlated with ALAD levels in another study (Gurer-Orhan et al 2004 ;Conterato et al 2013 ).…”
Section: Lead-induced Oxidative Stress In Occupationally Exposed Popumentioning
confidence: 74%
“…The reduction in Hb may be related to inhibition of its biosynthesis through the inhibition of δ-aminolevulinic acid synthase, δ-ALA dehydratase and ferrochelatase by Pb 40 . Additionally, Pb can bind with RBCs and inhibits pyruvate kinase "keeps cellular energy homeostasis" 42 and pyrimidine 5′-nucleotidase (essential for RBCs www.nature.com/scientificreports/ maturation) 43 . The inhibition of these enzymes destabilizes the RBCs membrane and decreases its fluidity leading to a shortage of the erythrocyte life span, hemolytic anemia, and ROS generation 42,43 .…”
Section: Discussionmentioning
confidence: 99%